Hubungan Pengelolaan Pengetahuan dengan Ketercapaian Program Sanitasi Total Berbasis Masyarakat - Yobi Sanjaya; Tasnim Tasnim; Erwin Azizi Jayadipraja (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Total Community Sanitation, from now on referred to as STBM, is a clean and healthy lifestyle that is used as a reference in implementing STBM. This study aimed to determine the relationship between the management of the achievement of the Community-Based Total Sanitation program at the Konawe District Health Center. This type of research is quantitative, using a cross-sectional design, collecting, analyzing, and describing information and data systematically, simultaneously increasing understanding of certain phenomena. The results of the variable analysis obtained the value of the Chi-Square test for knowledge management with a value of X Count 18.72 > from 3.84 or X table with a p-value of 0.529, which means it has a strong relationship. This study concludes that there is a significant relationship between the independent and dependent variables. To increase access to sanitation needs, it is recommended that the puskesmas coordinate with the local government in providing access to sanitation.